THE INSTANCES OF AN ARCHAIC MELODIC PATTERN IN CAROLS - Ilona SZENIK (Studia Universitatis Babeş-Bolyai. Musica)
Starting from the findings of previous studies, which have proved the long existence of the melodic category, in which the finale is situated on the fifth step of the six-cord scale, in this paper, the investigation is expanded onto the instances taken by this phenomenon in the repertoire of Romanian carols. The songs are grouped into general profile patterns. Groups and subgroups are constituted, on the basis of correlating the following criteria: architectonic patterns, sound structure and pitch of final cadences. From the findings, it follows that the finale on the fifth step is just one of the possibilities. Despite the variety of instances, there is a tight connection amongst the different melodic categories, due to the use of elements of common musical language.